Implementation of Parenting Education Program in Kindergarten - Amini, Mukti (Universitas Negeri Semarang, 2017)
This study aimed at getting an overview of ​​the type of parental education program that have been implemented, getting an overview of parental interest in parental education programs, and getting an overview of the strengths and weaknesses of parental education program that has been running in kindergartens in the region of South Tangerang. This study is explorative with descriptive analysis. The research location was in Pamulang and Serpong, sub district of South Tangerang, Banten. The research subjects are 49 kindergarten principals and teachers. The finding of the research showed that of the type of parental education program varied, but not all types of programs have been done. The Interests of parents to be involved in the parental education program which involves parents in kindergarten were quite high. The main strength of the parental education programs is the theme that meets the needs of parents. It can be a solution for them in solving the problem of child development. The main weakness in parental education program is the lack of parents presence on the program implemented. Therefore, the kindergartens need to think about a better strategy so that participation of parents in parental education programs would be optimal. Moreover, the principals and teachers in kindergartens also need to think about a better strategy to optimize the participation of parents in parental education programs.